Creation of a Sustainable Corporate Brand Identity : in an electrical industrial family company - Perkkiö, Heleena (My University, 2023)
Businesses have a crucial role to play in the green transition, which requires research and development, investment, innovation, and technologies. With energy-intensive production, long transport distances, and products that consume electricity throughout their life cycle, the electrical industrial sector has significant potential to turn the value chain towards sustainable development. The corporate brand identity is reflected in all its communications and activities, as it is the heart of the company strategy. Therefore, a sustainable corporate brand identity is the force that drives the operations and communication of the company in a sustainable direction and strengthens the competitive advantages of the company. The purpose of this thesis was to explore how to create a sustainable corporate brand identity in a family company operating in the electrical industry. More specifically, the thesis established the basis for a conceptual framework applicable to the electrical industry and was contracted to Sg Armaturen AS. The research was executed using a qualitative action research method. The theoretical framework covered B2B branding, corporate identity, and brand identity, as well as sustainability, focusing on the environmental dimension. It took into account the specificities and requirements of the sector. Empirical data was collected through semi-structured interviews with employees of the parent company and one subsidiary. The study suggests as a conclusion that electrical industrial companies can achieve a sustainable corporate brand identity. Defining a corporate brand identity and integrating sustainability into the corporate strategy are considered essential prerequisites. Successful implementation of sustainability, such as Circular Economy, Life Cycle Thinking, and the Sustainability Development Goals, will support the creation of a sustainable corporate brand identity. Similarly, family firm values are seen as reinforcing a sustainable corporate brand identity. Intern and extern communication are crucial parts of sustainable corporate brand identity. This work provides new contributions to both the marketing brand literature and corporate management. The main practical contribution of this study is the Sustainable Brand Identity Circle -process model which was developed based on the literature and applied to the contracting company using information from the empirical findings. This model can be utilized not only by the contracting company but also by other companies in the electrical industrial sector. This process model also contributes to the theoretical discourse and research on marketing through the development of a conceptual theory.

Yrityksillä on keskeinen rooli vihreässä siirtymässä, johon tarvitaan tutkimus- ja kehitystyötä, investointeja, innovaatioita ja teknologioita. Energiaintensiivisen tuotannon, pitkien kuljetusmatkojen ja koko elinkaaren ajan sähköä kuluttavien tuotteiden vuoksi sähköteollisuudenalalla on huomattavat mahdollisuudet kääntää arvoketju edistämään kestävää kehitystä. Yrityksen brändi-identiteetti heijastuu yrityksen kaikessa kommunikaatiossa ja toiminnassa, koska se on yrityksen strategiassa määritelty sydän. Siksi kestävä yritysbrändi-identiteetti on voima, joka ohjaa yrityksen toimintaa ja kommunikaatiota kestävään suuntaan ja vahvistaa yrityksen kilpailuetua. Opinnäytetyön tavoitteena oli selvittää, miten kestävä yritysbrändi-identiteetti luodaan sähköteollisuudessa toimivassa perheyrityksessä. Tarkemmin ottaen tutkielmassa luotiin perusta sähköteollisuuden alalla sovellettavalle käsitteelliselle kehykselle ja se toteutettiin toimeksiantona Sg Armaturen AS:lle. Tutkimus toteutettiin laadullista toimintatutkimusmenetelmää käyttäen. Teoreettinen viitekehys käsitteli B2B-brändiä, yritysidentiteettiä ja brändi-identiteettiä sekä kestävää kehitystä, jossa keskityttiin ympäristönäkökulmaan ja otettiin huomioon alan erityispiirteet ja vaatimukset. Empiirinen aineisto kerättiin puolistrukturoitujen haastattelujen avulla emoyhtiön ja yhden tytäryhtiön työntekijöitä haastattelemalla. Johtopäätöksenä tutkimuksessa esitetään, että sähköteollisuuden yritykset voivat saavuttaa kestävän yritysbrändi-identiteetin. Olennaisina edellytyksinä pidetään yrityksen brändi-identiteetin määrittelyä ja kestävän kehityksen sisällyttämistä osaksi yritysstrategiaa. Kestävän kehityksen, kuten kiertotalouden, elinkaariajattelun ja kestävän kehityksen tavoitteiden menestyksellinen implementointi tukevat kestävän kehityksen mukaista yritysbrändi-identiteetin rakentamista. Samoin perheyrityksen arvot nähdään kestävää yritysbrändi-identiteettiä vahvistavina tekijöinä. Sisäinen ja ulkoinen viestintä ovat merkittävä osa kestävää yritysbrändi-identiteettiä.Tämä työ tarjoaa uutta tietoa sekä markkinoinnin brändikirjallisuudelle, että yritysjohdolle. Tärkein käytännönläheinen anti tässä tutkimuksessa on vastuullisen brändi-identiteetin ympyrä -prosessimalli, joka kehitettiin kirjallisuuden pohjalta ja jota sovellettiin tapausyritykseen empiriasta nousseen informaation avulla. Tätä mallia voivat hyödyntää paitsi toimeksiantajayritys, myös muut sähköalan tuotantoyritykset. Tämä prosessimalli kontribuoi myös markkinoinnin teoreettista keskustelua ja tutkimusta konseptuaalisella teorian kehittämisellä.
Keywords: corporate brand identity, sustainability, family firm yritysbrändi-identiteetti, kestävä kehitys, perheyritys